2010
DOI: 10.3109/17435390.2010.500444
|View full text |Cite
|
Sign up to set email alerts
|

Potential pulmonary effects of engineered carbon nanotubes:in vitrogenotoxic effects

Abstract: The development of novel engineered nano-sized materials is a rapidly emerging technology with many applications in medicine and industry. In vitro and in vivo studies have suggested many deleterious effects of carbon nanotube exposure including granulomatous inflammation, release of cytosolic enzymes, pulmonary fibrosis, reactive oxygen damage, cellular atypia, DNA fragmentation, mutation and errors in chromosome number as well as mitotic spindle disruption. The physical properties of the carbon nanotubes mak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
50
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 88 publications
(53 citation statements)
references
References 99 publications
3
50
0
Order By: Relevance
“…Specifically, our study shows that after 24 h exposure, MWCNTs localize at the cell nucleus, with nanotube localization inducing changes in the nucleus mechanics by increasing its stiffness and overall Young's modulus with more than 36.6% than for control cells (either cells exposed to 1 h acids-washed MWCNTs for 1 h or to the control cells). Combining our data with previous reports that indicate that MWCNTs interact with microtubules, [22,46] the mitotic spindle, [22] DNA and cell division apparatus, [17,18] we propose now that the observed stiffness due to exposure to 1 h acids-washed MWCNTs could lead the reorganization of the three-dimensional cellular cytoskeletal network. Such reorganization could potentially disrupt the mitotic spindle, [22] inducing errors in chromosome numbers to be propagated through further cellular division [19] as characteristics of cancer cells.…”
supporting
confidence: 52%
See 2 more Smart Citations
“…Specifically, our study shows that after 24 h exposure, MWCNTs localize at the cell nucleus, with nanotube localization inducing changes in the nucleus mechanics by increasing its stiffness and overall Young's modulus with more than 36.6% than for control cells (either cells exposed to 1 h acids-washed MWCNTs for 1 h or to the control cells). Combining our data with previous reports that indicate that MWCNTs interact with microtubules, [22,46] the mitotic spindle, [22] DNA and cell division apparatus, [17,18] we propose now that the observed stiffness due to exposure to 1 h acids-washed MWCNTs could lead the reorganization of the three-dimensional cellular cytoskeletal network. Such reorganization could potentially disrupt the mitotic spindle, [22] inducing errors in chromosome numbers to be propagated through further cellular division [19] as characteristics of cancer cells.…”
supporting
confidence: 52%
“…[18,19] For instance, our recent studies have shown that 24 to 72 h exposure of epithelial cells to SWCNTs induced centrosome fragmentation and aneuploidy [18,20] similar to the genotoxin vanadium pentoxide. [21] Likewise, cellular exposure to MWCNT disrupted the mitotic spindle by association with microtubules, [22] induced polyploidy [17] and changes in chromosome number in a fashion similar to crocidolite asbestos. [20,23,24] CNTs genotoxicity has been attributed to a variety of factors including metal impurities, length, size, number of walls, surface area, dispersion, and/or CNTs surface functionalization.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…39 However, CNFs generate significant radicals and are more genotoxic than SWCNTs. 43 Sargent et al 44 reported that SWCNTs disrupt centrosomes in dividing lung epithelial cells resulting in multipolar mitosis and aneuploidy. MWCNTs have also been shown to interact with centrosomes preventing normal migration to mitotic poles and resulting in monopolar mitosis.…”
Section: In Vitro Responses To Cntsmentioning
confidence: 99%
“…Such low doses also reveal CNT-induced cell transformation and aneuploidy instead of cell death. 44,49 …”
Section: Relationship Between In Vivo and In Vitro Responses To mentioning
confidence: 99%